The Circle of Unity: The power of symbols in a team sport context - O'Hallarn, Brendan; Morehead, Craig; Slavich, Mark; Cintron, Alicia (Journal of Intercollegiate Sport, 2021)
Modern-day political discord has led to a recent spate of athletes using their platform to make statements about America. One under-researched aspect to modern sport activism is the study of the symbols themselves, such as the controversial kneeling during the national anthem by National Football League players, statement-making pregame apparel worn by National Basketball Association stars, and other political statements. This case study examines a 2016 activist display by Old Dominion University’s football team, known as the Circle of Unity. The display, performed before most games that season, began as a form of protest by team captains, and morphed into a gesture that was celebrated across the political spectrum. Through the lens of both Symbolic Interactionism (SI) and Critical Race Theory (CRT), the current study seeks to uncover the impetus, meaning, and ultimate impact of the symbol on a variety of stakeholders. Examining the symbol used—players and coaches standing in a circle, facing out, holding hands and raising them to the sky—can further contextualize the challenging role that student-athletes have in finding their voice to speak on issues they care about in a divided America.